No on Prop 6 Fundraiser in Watkins Family Backyard - Watkins, Howard::::::::: (1978)
Ch 24 TV camera operator Ernesto Moreno, Ed Asner, Fresno Bee Reporter Gene Rose, Art Agnos, Karen Humphrey David Smith, Nancy Currier, ?, at check-in table